Recent Advances in Mathematical Research and Computer Science Vol. 4 - Ferreira, M. A. M. (2021)
This book covers key areas of Mathematical Research and Computer Science. The contributions by the authors include model assistance, model calibration, semiparametric model, penalized splines, Gambler’s ruin, random walks, Brownian motions, reserves, pensions fund, Two dimensional wave equation, one dimensional heat equation, unsteady motion, Navier Stoke’s equation, incompressible flow, Auxiliary attribute, mean square error, Fixed effects, random effects, coefficient of determination, panel data and Hausman test, space-action, Dual bi-directional heuristic, heuristic, global optimum solution, bi-directional heuristic, optimum solution, multi-start heuristic, Gaussian distribution, channel capacity, directed divergence, information theory, uniform distribution, geometric algebra, limit cycle, measure, Gagliardo-Nirenberg, Prekopa-Leindler, Debreu, Brouwer, Lusin, transcendental equation, lebesgue integral, finite time blowup, NP-complete problem, polynomial algorithm, independent and identically distributed random variables, Optimal control, singular extremals, strengthened legendre-clebsch condition, Network reliability, probability-ready expression, multi-state system, multiple-valued logic, symbolic expression, multi-state delivery network. This book contains various materials suitable for students, researchers and academicians in the field of Mathematical Research and Computer Science.